An experimental analysis of grandfathering vs dynamic auctioning in the EU ETS - Botelho, Anabela (2017)
This study constitutes a first attempt to experimentally test the performance of a 100% auction versus a 100% free allocation of CO2 permits under the rules and parameters that mimic the EU ETS (imperfect competition, uncertainty in emissions’ control, and allowing banking). It also incorporates a first attempt to include in the analysis measures of the risk preferences of subjects participating in emission permits experiments. Another distinctive feature of this study is the implementation of a theoretically appropriate auction format for the primary allocation of emission permits. Our experimental results indicate that the EU ETS has the potential to reduce CO2 emissions, achieving targets considerably more restrictive than the current ones at high efficiency levels, both with auctioned and free emission permits. Auctioning, however, reveals a clear potential to do better than grandfathering the initial allocation of permits. In addition, the results reveal that concerns about undue scarcity, and corresponding high prices, in secondary markets generated by a primary auction market are not warranted under the proposed dynamic auction format.